A Connection between Transport Phenomena and Thermodynamics - Swaney, Ross; Bird, R. Byron (Chemical engineering education, 2017)
Although students take courses in transport phenomena and thermodynamics, they probably do not ask whether these two subjects are related. Here we give an answer to that question. Specifically we give relationships between the equations of change for total energy, internal energy, and entropy of transport phenomena and key equations of equilibrium thermodynamics. It is revealing to see how the irreversible processes of heat conduction and viscous flow in going from one thermodynamic state to another are accommodated in the derivation of dU TdS pdV.